Strategic Technology Choice and Capacity Investment Under Demand Uncertainty - Goyal, Manu; Netessine, Serguei (Management Science, 2007)
This paper studies the impact of competition on a firm’s choice of technology (product-flexible or product-dedicated) and capacity investment decisions. Specifically, we model two firms competing with each other in two markets characterized by price-dependent and uncertain demand. The firms make three decisions in the following sequence: choice of technology (technology game), capacity investment (capacity game), and production quantities (production game). The technology and capacity games occur while the demand curve is still uncertain, and the production game is postponed until after the demand curve is revealed. We develop best-response functions for each firm in the technology game and compare how a monopolist and a duopolist respond to a given flexibility premium. We show that the firms may respond to competition by adopting a technology which is the same as or different from what the competitor adopts. We conclude that contrary to popular belief, flexibility is not always the best response to competition—flexible and dedicated technologies may coexist in equilibrium. We demonstrate that as the difference between the two market sizes increases, a duopolist is willing to pay less for flexible technology, whereas the decision of a monopolist is not affected. Further, we find that a firm that invests in flexibility benefits from a low correlation between demands for two products, but the extent of this benefit differs depending on the competitor’s technology choice. Our results indicate that higher demand substitution may or may not promote the adoption of flexibility under competition, whereas it always facilitates the adoption of flexibility without competition. Finally, we show that contrary to intuition, as the competitor’s cost of capacity increases, the premium a flexible firm is willing to pay for flexibility decreases.